2023
DOI: 10.3390/foods12112214
|View full text |Cite
|
Sign up to set email alerts
|

Food-Waste Valorisation: Synergistic Effects of Enabling Technologies and Eutectic Solvents on the Recovery of Bioactives from Violet Potato Peels

Abstract: The recovery of valuable bioactive compounds from the main underutilised by-products of the food industry is one of the greatest challenges to be addressed in circular economy. Potato peels are the largest waste generated during potato processing. However, they could be a potential source of valuable bioactive compounds, such as polyphenols, that can be reused as natural antioxidants. Currently, environmentally benign enabling technologies and new types of non-toxic organic solvents for the extraction of bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The extracts with DESs also presented better results in terms of antimicrobial activity [170,179,184], antiproliferative activity in tumour Caco-2 cells and normal human keratinocyte cells [185], lower toxicity and increase bioavailability of the target compounds when administered to rats [186], higher antioxidant, [184] and anti-inflammatory effects as well as inhibitory effects against αglucosidase and pancreatic lipase [187] when compared to the extracts from the traditional solvents. The enhanced biological activity of the DESs extracts can be explained by the higher content of bioactive compounds [187,188].…”
Section: Deep Eutectic Solvents For the Extraction Of Bioactive Compo...mentioning
confidence: 94%
“…The extracts with DESs also presented better results in terms of antimicrobial activity [170,179,184], antiproliferative activity in tumour Caco-2 cells and normal human keratinocyte cells [185], lower toxicity and increase bioavailability of the target compounds when administered to rats [186], higher antioxidant, [184] and anti-inflammatory effects as well as inhibitory effects against αglucosidase and pancreatic lipase [187] when compared to the extracts from the traditional solvents. The enhanced biological activity of the DESs extracts can be explained by the higher content of bioactive compounds [187,188].…”
Section: Deep Eutectic Solvents For the Extraction Of Bioactive Compo...mentioning
confidence: 94%
“…The extracts with DESs also presented better results in terms of antimicrobial activity [ 165 , 174 , 179 ], antiproliferative activity in tumour Caco-2 cells and normal human keratinocyte cells [ 180 ], lower toxicity and increased bioavailability of the target compounds when administered to rats [ 181 ], higher antioxidant effects [ 179 ], and higher anti-inflammatory effects, as well as inhibitory effects against α-glucosidase and pancreatic lipase [ 182 ] when compared to the extracts from the traditional solvents. The enhanced biological activity of the DESs extracts can be explained by the higher content of bioactive compounds [ 182 , 183 ].…”
Section: Deep Eutectic Solvents For the Extraction Of Bioactive Compo...mentioning
confidence: 99%
“…Another important advantage of the extracts containing DESs is their stability. Some studies were performed to study this parameter and found that the DESs extracts have a longer shelf-life when compared with conventional solvents extracts [ 129 , 180 ]. This stabilization was due to the ability of the DESs to stabilize the phenolic compounds [ 185 ].…”
Section: Deep Eutectic Solvents For the Extraction Of Bioactive Compo...mentioning
confidence: 99%
“…Tomato is rich in flavones like chlorogenic acid, rutin, and quercetin [44,61]. Numerous phenolic compounds have been extracted from onion and tomato by-products using DESs, such as quercetin [58,60], kaempferol glycosides [59], and anthocyanins [62]. Additionally, DESs show high extraction efficiency in retrieving phenolic compounds from other vegetable by-products, like kale waste [63], bitter melon leaves [64], pepper leaves [65], and lotus leaves [66].…”
Section: Vegetable By-productsmentioning
confidence: 99%